TERAPI INGATAN MELALUI FOTO TEMUAN DAN KOLASE MIXED MEDIA: Memory Therapy Through Found Photos and Mixed Media Collage - Aji Susanto Anom Purnomo (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2023)
Memory plays a vital role for humans as historical beings. Man interprets his life in a space of time that continues in his memory. Humans also know the concept of forgetting, where memory repression is one of the leading causes. Repression is a memory activity in which past experiences are deliberately suppressed so that they do not surface. Guilt and traumatic events in childhood are just a few causes of such repressive activities. Photography as an art activity has a very close relationship with the function of memory. The beginning of the emergence of the photographic medium is related to the human desire to record memories from precious memories. The connection between photography and memory becomes more pronounced when photography becomes a medium of art therapy. Â Photography as a medium of art therapy is called the therapeutic photography approach. This approach is an exploration that will be carried out in this study. The subject of research that will be a vital instrument in this research is the experience of the researcher, who still leaves internal conflicts on him. The research method will use Fox's creative creation research method and conduct memory therapy through mixed media experimentation on the photo findings. The stages of this research are as follows: Observation stage, Data collection, Problem Identification and Formulation, Literature Study, Data Processing, Data Analysis, Exploration, Experimentation and Work Realization. This study aims to reveal the positive effects of the medium of photography as art therapy. The therapeutic process carried out is based on the activity of making and reading a narrative through photographic works. The narrative is constructed through re-accessing memory and self-reflection to find positive coping. With the positive effects caused by therapeutic photography, it is hoped that the repression experienced by research subjects will be reduced and reconcile internal conflicts. Keywords: art therapy, collage, found photograph, therapeutic photography